The Role of Workplace Environment in Shaping Workers' Innovative Behavior: Insights From Bibliometric Analysis - Nabillah, Nisfatun; Fatmawati, Indah; Nuryakin, Nuryakin (SENTRALISASI, 2025)
This study aims to analyze the role of the workplace environment in shaping innovative worker behavior. The method used in this research is a mixed method with a Literature Study (SLR) approach. The quantitative method in this research focuses on numerical or statistical data (e.g., number of publications, citation frequency, publication trends, and methodology trends). The qualitative method analyses the content of existing articles or literature (e.g., concepts, themes, and contexts underlying existing research). It identifies trends that may not be visible from mere numerical data. The data sources in this study were taken from the Scopus database and Google Scolar, which included the keywords “Workplace Environment” AND “Innovative Behaviour”. The study analyzed 79 articles published in reputable international journals from 2015-2023. The research found four main streams in the workplace environment and innovative behavior research: (1) a focus on individuals as agents of innovation, which dominated the 2015-2018 period; (2) an emphasis on the relationship between individuals and organizations that emerged in 2019-2020, where human resource management plays an essential role in supporting innovation; (3) attention shifted to organizations, focusing on collective innovation processes in 2021-2022; and (4); the most recent research (2023) again highlighted individuals as key catalysts of innovation, underlining the importance of the role of individuals in fostering creativity in the work environment.